Purification of SlREC2 from wild-type tomato leaflets using immunoaffinity chromatography and immunoprecipitation - Zhu, Lingling; Larkin, Robert M. (Frontiers in Plant Science, 2025)
The process of obtaining greater mechanistic insight into important traits that follows the linking of a gene to a trait can be impeded if the encoded protein has no known biochemical function or a vague biochemical function. In such instances, many researchers attempt to obtain insight into biochemical function by identifying other proteins that bind their protein of interest (POI). Particular methods may lead to the discovery of protein-protein interactions that are not physiologically meaningful. Other methods require the production of transgenic plants, which is impractical or impossible for many important crop plants. We present guidelines for purifying native proteins from wild-type plants because native proteins may stably associate with physiologically meaningful POI-binding proteins (POI-BPs). This strategy involves partially purifying native multisubunit protein complexes from wild-type plants and ultimately purifying native multisubunit protein complexes using immunoaffinity chromatography or immunoprecipitation with affinity-purified polyclonal antibodies raised against a recombinant POI. Proteins that copurify with a POI are candidate POI-BPs that can be identified using mass spectrometry. As an illustrative example, we developed polyclonal antisera against the REDUCED CHLOROPLAST COVERAGE 2 protein from tomato (Solanum lycopersicum L.) (SlREC2) and affinity purified the anti-SlREC2 antibodies. We used these antibodies to detect SlREC2 during the partial purification of SlREC2 using rapid batch binding and step gradient elution procedures involving SP Sepharose and Q Sepharose and to purify SlREC2 ultimately using immunoaffinity chromatography and in a distinct procedure using immunoprecipitation. The purified native SlREC2 was readily detectable in Coomassie blue-stained SDS gels and was unambiguously identified using mass spectrometry. We discuss critical parameters and potential technical problems and provide suggestions for developing procedures for purifying a variety of different native POIs with different properties from wild-type plants.